Changes in the Patient-Reported Outcomes Measurement Information System (PROMIS) scores following sacral neuromodulation for lower urinary tract symptoms - Elaine Minerva Jaworski; Derrick J. Sanderson; Matthew Gevelinger; Paula J. Doyle (Current Urology)
Abstract. Background. Sacral neuromodulation (SNM) treatment of refractory urinary symptoms is associated with quality of life improvements using disease-specific instruments. There is a paucity of information relating universal health outcomes to effective treatment of urinary symptoms. The objective was to analyze changes in Patient-Reported Outcomes Measurement Information System (PROMIS) item-bank scores following SNM for treating refractory lower urinary tract symptoms (LUTS). Materials and methods. This is a sub-analysis collected from an institutional review board approved, retrospective chart review evaluating changes between pre- and post-procedure PROMIS scores in subjects undergoing successful SNM implantation for refractory LUTS at a multidisciplinary adult continence clinic. The difference between pre- and post-procedure PROMIS scores was compared via two-sided Wilcoxon signed-rank test, with p <0.05 considered statistically significant. Results. Of the 29 subjects, most were female (89.66%), Caucasian (68.97%), nonsmokers (89.66%) with public insurance (62.07%). The median age was 63years and body mass index was 33.2kg/m2. Procedure indications included urinary urge incontinence (83%), mixed urinary incontinence (10%), retention (17.24%), and overactive bladder (3%). Pain Interference and Depression scores had a nonsignificant improvement from 64.2 (ranging 58.9–67.5) to 60.75 (ranging 55.2–67.2), p = 0.21, and 55.2 (ranging 51.5–59.9) to 53.4 (ranging 49.5–61.1), p = 0.33, respectively. Median Physical Function scores demonstrated nonsignificant worsening following implantation from 38.0 (ranging 34.7–40.9) to 36.1 (ranging 33.1–40.8) (p = 0.25). Twenty-one subjects (72%) reported an improvement in at least 1 PROMIS item-bank with 6 subjects (21%) reporting no improvement in any of the item-banks. Conclusions. Treatment of refractory LUTS with SNM resulted in no statistically significant changes in the PROMIS item-banks of Physical Function, Pain Interference, or Depression. Further prospective investigation is necessary to delineate the relationship of the self-reported universal-health outcomes in the treatment of LUTS.